Exploring the potential of metallic peroxide granules for the in-situ mitigation of cyanoHABs - Antoniou, Maria G.; Keliri, Eleni; Christofi, Manolis; Efstathiou, Nektarios (My University, 2022)
Several chemical treatments have been tested over the years for the mitigation of blue-green algae including harmful pesticides and algaecides. The latter ones are prohibited to be used in many US states and the European Union, hence alternative treatments that are more environmentally friendly are currently explored. Hydrogen peroxide (HP) is characterized as an environmentally friendly approach as it does not produce harmful residues and an increased sensitivity of cyanobacteria to HP treatment compared with green algae was reported. However, dense blooms require high doses of HP that can disrupt the remaining ecosystem. To address this problem, slow releasing HP metallic granules were used as an alternative to liquid HP solution. Specifically, calcium peroxide granules were applied in surface water from Kouris Reservoir, Cyprus. This study examined the HP releasing properties with varying pH values, their mitigation efficiency on Microcystis sp. bloom in comparison with HP liquid application and their toxicity on Echinogammarus veneris sp. in a range of concentrations. Results showed that treatment with granules was efficient even at the low concentration of 0,5 g/L while the equivalent liquid HP concentration was not. Toxicity studies on zooplankton indicated that the low concentrations of the granules applied were not toxic.